Qualitative Analysis of Onsite Sanitation Challenges in an Urban Setting: The Case of Jimma Town, Ethiopia - Dereje Oljira Donacho; Gudina Terefe Tucho; Negasa Eshete Soboksa; Mekonnen Haile Faro; Abebe Beyene Hailu (SAGE Publishing, 2023)
On-site sanitation is the most popular sanitation option for households in many African countries, including Ethiopia. Despite the option being common, there are challenges attributed to the sustainability of those facilities. This community-based exploratory study aimed to explore the challenges in the provision of safe urban on-site sanitation in Jimma town, Ethiopia. Data were collected through key informant semi-structured interviews, transit walks through the village, and focus group discussion (FGD). The FGD was audio recorded and notes were taken by experts. Records and notes were transcribed separately and thematically analyzed. Three major themes or challenges were discovered. Accordingly, the first theme was the community's perception and taboos surrounding human waste. The second theme was urban land use and informal settlements. Ensuring standards separately for sanitation facilities is difficult because of the expansion of illegal settlements. The third theme was poor sanitation planning, operation and maintenance, and institutional setting. Urbanization without infrastructure generally has a complex nature that leads to a fragile sanitation situation in the future. The results suggest the need for multi-dimensional system development and a collaborative sanitation master plan. Furthermore, interventions aimed at breaking the taboo on human waste as a sanitation platform may turn challenges into opportunities.